1975
DOI: 10.1111/j.1476-5381.1975.tb07369.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Tachycardia Produced by Intracerebro‐ventricular Injections of Isoprenaline in Mice

Abstract: I Isoprenaline, 3.5-20 ng, injected intracerebroventricularly in atropinized mice under pentobarbitone anaesthesia produced a dose-dependent tachycardia. 2 Pretreatment with either reserpine or pempidine blocked nervously-mediated tachycardia as shown by marked reduction of that due to stimulation of the spinal outflow in pithed mice. After pretreatment with these drugs, intracerebroventricular isoprenaline caused tachycardia of a similar degree and time course to that in mice not so pretreated. 3 Pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In previous experiments it has been demonstrated that following central administration, a p preciable amounts of ( -)-isoprenaline can escape from the CNS of the mouse (Burden & Parkes, 1975) and in some (Conway & Lang, 1974) but not in other (Bhargava, Mishra & Tangri, 1972) experiments in the dog. However, in the rat (Cohen et al, 1976) and cat (Day & Roach, 1973 Day, Poyser & Sempik, 1980) the i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments it has been demonstrated that following central administration, a p preciable amounts of ( -)-isoprenaline can escape from the CNS of the mouse (Burden & Parkes, 1975) and in some (Conway & Lang, 1974) but not in other (Bhargava, Mishra & Tangri, 1972) experiments in the dog. However, in the rat (Cohen et al, 1976) and cat (Day & Roach, 1973 Day, Poyser & Sempik, 1980) the i.c.v.…”
Section: Discussionmentioning
confidence: 99%